SYNTHESIS OF MACROPORE CONTAINING CATALYST FOR RESIDUE CATALYTIC CRACKING - Ekananda, Rizki
Fluid Catalytic Cracking (FCC) is one of the leading conversion technologies used in the petroleum processing industry. FCC is one of the largest gasoline-producing units among all process units in a petroleum processing complex. Catalyst synthesis was carried out using a spray dryer to form FCC catalyst particle composites. Catalyst is made by combining the zeolite, matrix and filler components to produce FCC catalyst composite with an almost perfect spherical morphology. The research obtained a procedure for making FCC catalyst composites that can guarantee the production of composites with suitable physical characteristics. The bulk composite with suitable particle size distribution in the range of 80-120 microns is required in every FCC catalyst performance testing method relevant to FCC catalysts evaluation, both at Advance Cracking Evaluation (ACE) pilot plant, riser plant, and commercial unit trial. In addition, the procedure is obtained for formulating the catalyst components to suit the target zeolite to matrix ratio required for the ecat so that optimal performance can be achieved when applied to commercial-scale units. The obtained relationship related to the ratio of silica to alumina in the matrices can assist in the catalyst formulation stages to achieve performance targets and cracking selectivity for specific products in their application in commercial FCC units. The stages of forming the catalyst composite after mixing the catalyst matrix components resulted in an interaction with the pore structure of the matrix. Another approach is needed to correlate the properties of the matrix components to estimate the performance of the FCC catalyst composite. The difference in composition based on the zeolite/matrix ratio (Z/M) resulted in differences in the mesoporous and microporous areas. The micropore area has a linear correlation with the zeolite composition, while the mesopore area has a linear correlation with the matrix composition. Correlation using weighted yield, which combines cracking performance, gasoline octane, and price specifications of each cracking product, is used to determine the best ecat zeolite surface area/matrix surface area (ZSA/MSA) target capable of producing the largest operational margin. Based on this correlation, the required ZSA/MSA to produce optimal performance is in the range of 1.7-2.2. Slurry feedstock made with Z/M 2.06 on a large scale can produce FCC catalyst composites with ZSA/MSA lab paint of 1.94. This FCC catalyst composite made on a large scale has performance that can meet all the targets required by Refinery Unit III Plaju, namely gasoline 52.51 wt-% compared to the minimum target of 50.5 wt-%, and propylene 10.54 wt-% compared to the minimum target of 5.8-6.1 wt-%. Correlations and approaches for this FCC catalyst composite formulation can be further developed to accommodate different types and properties of raw materials. The approach used by existing commercial catalyst manufacturers is often part of the patents or trade secrets, so the results achieved with this research are expected to be helpful in the ultimate goal of building a sustainable FCC catalyst industry in Indonesia.